ANALISIS KRONOFARMAKOLOGI PENGGUNAAN PARACETAMOL PADA PASIEN COVID-19 DI RSUD DR. SOEDOMO TRENGGALEK - Prasetyawan, Fendy; Saristiana, Yuneka; Muslikh, Faisal Akhmal; Mildawati, Ratna; Oktadiana, Isma; Arifin, Chandra; Rofiq, Abd; Febriana, Laela; Besan, Emma jayanti; Fadel, Muhammad Nurul (Noble Cendekia Indonesia, 2024)
The global COVID-19 pandemic has presented complex challenges to global health. Dr. Soedomo Regional General Hospital in Trenggalek has actively engaged in managing COVID-19 patients. This study aims to analyze the chronopharmacology of paracetamol usage in COVID-19 patients at the hospital, focusing on the body's biological response to the drug at various time points within the 24-hour cycle. In the treatment of COVID-19, the use of paracetamol has become a primary strategy for addressing symptoms such as fever. However, it is crucial to understand how the timing of paracetamol administration can influence the body's response to the treatment. A chronopharmacological study involving 100 patients analyzed body temperature before and after therapy at three different times: 08:00 AM, 04:00 PM, and 10:00 PM. The results revealed a significant decrease in body temperature after therapy, particularly at 04:00 PM. These findings support the concept of